Accurate iron quantification in colloids and nanocomposites by a simple UV-Vis protocol - Torras, Miquel (2020)
The selection and comparative study is reported of calibration curves to quantify iron by a simple UV-Vis protocol based on the formation of iron (III) chloride complexes. The reliability of each calibration curve was evaluated using statistical and analytical parameters. The robustness of each calibration curve using superparamagnetic iron oxide nanoparticles (SPIONs) of different sizes and surface functionalization is demonstrated . We have also evaluated the effect of the particle coating and estimated the minimum time to ensure the full oxidation of iron (II) to (III) in sample solutions. Results from UV-Vis are comparable with those obtained from ICP-OES and from other spectroscopic techniques to quantify the iron. We advocate the proposed protocol as a simple and non-expensive route to determine accurately the iron content in colloidal and nanocomposite iron-based materials.